2015
DOI: 10.1180/claymin.2015.050.5.01
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid systems based on organic dyes and clay minerals: Fundamentals and potential applications

Abstract: This review summarizes several aspects of the interactions between organic dyes and clay minerals, and presents some interesting properties of hybrid materials based on these components. It explains the basic phenomena and photophysical properties of dye/clay mineral hybrid systems (DCHS) while examining the role of clay minerals in them. A brief history of using dyes as tools for clay research and on traditional materials based on DCHS is presented. Metachromasy, the phenomenon of colour change related to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 153 publications
(191 reference statements)
0
22
0
3
Order By: Relevance
“…The idea is to transfer to modern materials the environmental resilience and other interesting properties of ancient materials, like Roman cements or the Blue Maya pigment, typically based on minerals. Indeed inclusion compounds of engineered clays are beginning to show actual potential as eco‐friendly functional materials . Such progress was also fostered by modeling studies – that suggested, for example, to contrast the worsening in the mechanical properties of a clay (caused by the incorporation of dyes) via the co‐adsorption of surfactants in the interlayer space of the clay .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The idea is to transfer to modern materials the environmental resilience and other interesting properties of ancient materials, like Roman cements or the Blue Maya pigment, typically based on minerals. Indeed inclusion compounds of engineered clays are beginning to show actual potential as eco‐friendly functional materials . Such progress was also fostered by modeling studies – that suggested, for example, to contrast the worsening in the mechanical properties of a clay (caused by the incorporation of dyes) via the co‐adsorption of surfactants in the interlayer space of the clay .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed inclusion compounds of engineered clays [47] are beginning to show actual potential as eco-friendly functional materials. [773][774][775][776][777][778] Such progress was also fostered by modeling studies -that suggested, for example, to contrast the worsening in the mechanical properties of a clay (caused by the incorporation of dyes) via the co-adsorption of surfactants in the interlayer space of the clay. [779][780][781] Taking inspiration from Blue Maya, the indigo molecule was recently encapsulated into zeolite L microcrystals yielding an exceptionally robust colorant: [782] the insight from simulations [191] was instrumental for the successful blockage of the crystal terminations.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that clay minerals play an important role in the occurrence of specific photophysical phenomena such as resonance energy transfer and luminescence quenching, and may influence various reactions, such as conformational changes in dye molecules, photochromism, photoisomerization, photosensitization and other photochemical processes (for review see Bujdak 2015).…”
Section: Clay Minerals (Particularly the Swelling-expanding Ones)mentioning
confidence: 99%
“…The first 11 one is to adsorb excess cationic surfactants [21], such as hexadecyltrimethylammonium or 12 cetylpyridium chloride. These molecules bear a positively charged hydrophilic head (usually 13 through the presence of an ammonium functional group) and a neutral hydrophobic tail. The 14 head can be adsorbed onto the negatively charged surface to form the first layer of the 15 surfactant, and additional surfactant adsorption will then yield a positive surface charge [21].…”
mentioning
confidence: 99%